Just a stupid little question that I don’t understand how to solve, & would very much appreciate any kind of help, cheers.
$\displaystyle F(x)=2x^2+3x-1 $
find in simplest form: $\displaystyle F(x+4)$
If it can be helped, we don't like doing people's work for them around here. It won't help you as much as if you tried it yourself.
$\displaystyle F(x + 4) = 2(x + 4)^2 + 3(x + 4) - 1$
.............$\displaystyle = 2 \left(x^2 + 8x + 16 \right) + 3x + 12 - 1$
.............$\displaystyle = 2x^2 + 16x + 32 + 3x + 11$
.............$\displaystyle = 2x^2 + 19x + 43$
Now that wasn't so hard was it?